Coating liquid, manufacturing method of component, and component

JP7634068B2Active Publication Date: 2025-02-20CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023205466
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-07
Filing Date
2023-12-05
Publication Date
2025-02-20
Estimated Expiration
2039-11-01

Smart Images

  • Figure 0007634068000002
    Figure 0007634068000002
  • Figure 0007634068000003
    Figure 0007634068000003
  • Figure 0007634068000004
    Figure 0007634068000004
Patent Text Reader

Abstract

To provide a coating liquid that is able to form a highly reliable film capable of suppressing an increase in haze for a long period of time even when exposed to an outdoor environment and maintaining hydrophilicity.SOLUTION: Provided is a coating liquid comprising silica particles, a silicate hydrolysis-condensation product, and a solvent, wherein the solvent comprises: at least one first solvent selected from a group consisting of ethers, esters, aliphatic or alicyclic hydrocarbons, aromatic hydrocarbons, ketones, chlorinated hydrocarbons, and aprotic polar solvents; and at least one second solvent selected from a group consisting of monohydric alcohols, dihydric or more alcohols, and ether alcohols.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating liquid, a method for producing a member, and a member. [Background technology]

[0002] In recent years, for crime prevention purposes, surveillance cameras have been installed in various locations such as stores, hotels, banks, and train stations. Surveillance cameras are installed by attaching them to ceilings, exterior walls, pillars, etc. using installation parts, or by embedding them in the ceilings, exterior walls, pillars, etc.

[0003] A transparent protective cover that does not interfere with imaging is attached to the surveillance camera body to protect it from the surrounding environment. Resin materials such as polycarbonate and acrylic resin, which have excellent transparency and impact resistance, are used for the protective cover. In the case of surveillance cameras installed outdoors, water droplets from rain and condensation adhere to the protective cover and distort or blur the image, so technology to prevent water droplets from adhering by providing a hydrophilic film on the protective cover is widely used.

[0004] Patent Document 1 proposes a hydrophilic film in which a silica particle film having high hydrophilicity and high adhesive strength is obtained by infiltrating a silica sol into a resin substrate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-203774 A Summary of the Invention [Problem to be solved by the invention]

[0006] Generally, when a resin substrate such as polycarbonate or acrylic resin used for a protective cover of a security camera or the like is installed outdoors for a long period of time, it deteriorates due to sunlight and cracks such as crazing occur. Therefore, even when a hydrophilic film is formed on the protective cover, cracks also occur in the hydrophilic film due to the occurrence of cracks in the resin substrate of the protective cover, and there is a problem that the captured image is distorted due to an increase in haze. In addition, there is also a problem that if the cracks extend, the hydrophilic film falls off the protective cover and hydrophilicity cannot be maintained.

[0007] Therefore, it is preferable that the hydrophilic film provided on the protective cover can suppress the occurrence of cracks, suppress an increase in haze, and maintain hydrophilicity when installed outdoors for a long period of time. However, the hydrophilic film having the configuration proposed in Patent Document 1 cannot suppress the deterioration of the base material caused by sunlight when installed outdoors for a long period of time, and therefore cannot suppress the occurrence of cracks in the hydrophilic film, cannot suppress an increase in haze, and cannot maintain hydrophilicity for a long period of time. [Means for solving the problem]

[0008] The present invention has been made in consideration of the above problems, and provides a coating liquid capable of forming a component having a hydrophilic coating that suppresses the occurrence of cracks in the hydrophilic film when installed outdoors for a long period of time, suppresses an increase in haze, and maintains hydrophilicity.

[0009] The coating liquid according to the present invention comprises: chain-like A coating liquid containing silica particles, a silicate hydrolysis condensate, and a solvent, the solvent being at least one first solvent selected from the group consisting of ethers, esters, aliphatic or alicyclic hydrocarbons, aromatic hydrocarbons, ketones, chlorinated hydrocarbons, and aprotic polar solvents, and at least one first solvent selected from the group consisting of monohydric alcohols, dihydric or higher alcohols, and ether alcohols. and has a boiling point lower than that of the first solvent. A second solvent, and the content of the silicate hydrolysis condensate is 3 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total of the chain silica particles and the silicate hydrolysis condensate. It is characterized by:

[0010] Further, a method for producing a member according to the present invention includes a step of providing the coating liquid on a resin substrate, curing the coating liquid, and resin forming a mixed layer on a substrate, wherein the mixed layer has a thickness of 20 nm or more and 160 nm or less, and the thickness variation in a range of 1 μm length along the surface of the resin substrate in a cross section of the mixed layer in the thickness direction is 15% or less.

[0011] Further, a member according to the present invention is a member produced by the above-mentioned production method. Effect of the Invention

[0012] According to the present invention, it is possible to provide a coating liquid capable of forming a highly reliable hydrophilic film that can suppress an increase in haze and maintain hydrophilicity for a long period of time even when exposed to an outdoor environment. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic diagram showing a cross section in a thickness direction of one embodiment of a transparent member according to the present invention. [Diagram 2] 1 is a schematic diagram showing an embodiment of an imaging device according to the present invention. [Diagram 3] 1 is a schematic diagram showing an example of the configuration of an imaging device according to the present invention; [Figure 4] 2 is an image of a cross section of the transparent member produced in Example 1 observed by a scanning transmission electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. Note that the present invention is not limited to the following embodiments, and appropriate modifications can be made without departing from the spirit of the present invention.

[0015] <Transparent materials> 1 is a schematic diagram showing a cross section in the thickness direction (parallel to the normal line of the substrate surface) of one embodiment of a transparent member according to the present invention. In the figure, a transparent member 10 according to the present invention has a hydrophilic coating formed on a resin substrate 16, the hydrophilic coating being composed of a porous layer 14 and a mixed layer 15 in which the porous layer penetrates into the resin substrate 16. In the present invention, "transparent" means a property having a visible light transmittance of 20% or more.

[0016] The porous layer 14 contains a plurality of silica particles (silicon oxide particles) 12 and a binder 11 interposed between the plurality of silica particles 12. The plurality of silica particles 12 are fixed to one another by the binder 11, and are made porous by voids 13 formed between the silica particles 12 and between the binder 11.

[0017] When a conventional hydrophilic film formed on a resin substrate is placed in an outdoor exposure environment, the hydrophilic film formed on the resin substrate is subjected to stress due to the following two phenomena, causing cracks. (1) The surface of the resin substrate is oxidized and deteriorated by sunlight and oxygen. (2) The resin base material expands and contracts due to water absorption from rain and temperature changes due to sunlight.

[0018] In contrast, with the above-mentioned configuration, first, the resin substrate 16 is covered with the mixed layer 15, thereby reducing the surface area of ​​the resin substrate 16 exposed to the surface, thereby preventing oxidation degradation of the resin substrate 16 and alleviating stress associated with expansion and contraction of the resin substrate 16. Furthermore, the silica particles in the mixed layer 15 and the porous layer 14 have a network structure, which alleviates stress associated with oxidation degradation of the resin substrate 16 and suppresses the occurrence of cracks in the resin substrate 16. As a result, the transparent member according to the present invention can suppress the occurrence of cracks in the hydrophilic coating, suppress an increase in haze for a long period of time, and maintain hydrophilicity even when installed in an outdoor environment.

[0019] Each layer will be described in detail below. <Porous layer> The porous layer 14 has a network structure in which the silica particles 12 are bonded to each other by the binder 11, and the voids 13 are included between the silica particles 12 and within the binder 11. In other words, the network structure is a structure formed by bonding the silica particles to each other with the binder. The porosity of the porous layer 14 is preferably 40% or more and 55% or less. When the porosity of the porous layer 14 is 40% or more, the internal stress of the film can be kept at a moderate level, so that the occurrence of cracks in the film during outdoor exposure can be suppressed, the increase in haze can be suppressed, and hydrophilicity can be maintained. In addition, when the porosity of the porous layer 14 is 55% or less, the haze of the hydrophilic film can be reduced, and transparency can be maintained. Furthermore, since the binder 11 and the silica particles 12 are hydrophilic, the porous layer 14 has hydrophilicity, and the contact angle of water on the surface of the porous layer 14 is 30° or less. In addition, the thickness of the porous layer 14 is preferably 100 nm or more and 800 nm or less. When the thickness of the porous layer 14 is less than 100 nm, the network structure of the mixed layer 15 and the porous layer 14 does not sufficiently suppress the occurrence of cracks in the resin substrate 16, and cracks occur in the film, making it impossible to suppress an increase in haze and maintain hydrophilicity. When the thickness of the porous layer 14 is more than 800 nm, the internal stress of the hydrophilic coating increases, causing cracks in the film, making it impossible to suppress an increase in haze and maintain hydrophilicity.

[0020] Here, the porosity of the porous layer 14 is a value representing the ratio of the volume of pores contained in the porous layer 14 to the volume of the porous layer 14. The porosity can be calculated using a spectroscopic ellipsometer according to Equation 1 from the refractive index of the porous layer, the refractive index of silica (1.46), and the refractive index of air (1.00). (Formula 1) Porosity=100×(refractive index of porous layer−1.46) ÷ (1.00−1.46)

[0021] Furthermore, it is preferable that the surface of the porous layer 14, i.e., the surface of the transparent member according to the present invention on which the porous layer 14 is provided, has an average surface roughness Ra of 2 nm to 10 nm. The average surface roughness Ra is calculated by a calculation method defined in JIS B 0601:2001, and when Ra is a small value, the porous layer 14 has a dense and uniform structure. Therefore, when Ra is 10 nm or less, even if the transparent member according to the present invention is placed outdoors for a long period of time, oxidation deterioration of the substrate and cracks in the hydrophilic coating can be suppressed, which is preferable. On the other hand, in terms of the relationship with the porosity, Ra is preferably 2 nm or more.

[0022] [Silica particles] The average particle size of the silica particles 12 is preferably 10 nm or more and 60 nm or less. When the average particle size of the silica particles 12 is 10 nm or more, the voids 13 formed between the particles can be appropriately enlarged, the desired porosity can be realized, and the internal stress of the film can be appropriately maintained. Therefore, the occurrence of cracks in the film can be suppressed during outdoor exposure environments, the increase in haze can be suppressed, and hydrophilicity can be maintained. In addition, when the average particle size of the silica particles 12 is 60 nm or less, the size of the voids 13 formed between the particles can be appropriately reduced, and the increase in haze can be suppressed without causing light scattering due to the voids 13 or the silica particles 12, which is preferable.

[0023] Here, the average particle diameter of the silica particles 12 is the average Feret diameter. This average Feret diameter can be measured by image processing of an image observed by a transmission electron microscope. As an image processing method, a commercially available image processing such as Image Pro PLUS (manufactured by Media Cybernetics, Inc.) can be used. In a predetermined image region, the contrast is appropriately adjusted if necessary, and the average Feret diameter of each particle is measured by commercially available particle measurement software, and the average value can be calculated.

[0024] The silica particles 12 may be solid or hollow silica particles, but chain-like silica particles in which these particles are linked together are particularly preferred. By using chain-like silica particles, the porosity can be increased without generating large voids. Chain-like silica particles may be mixed with solid or hollow silica particles. In the case of chain-like silica particles, the average particle size of the individual particles linked together is preferably 10 nm or more and 60 nm or less.

[0025] The silica particles 12 contain SiO2 as the main component, but may also contain metal oxides such as Al2O3, TiO2, ZnO, and ZrO2. However, if 30% or more of the silanol (Si-OH) groups on the surface of the silica particles 12 are modified with organic groups or compounded with other metals, the hydrophilicity is lost. The porous layer 14 made of such silica particles has low hydrophilicity and also has poor self-cleaning properties.

[0026] Therefore, in order to impart good hydrophilicity to the porous layer 14, it is preferable to use silica particles having silanol (Si-OH) groups remaining on 70% or more of the particle surface, and it is more preferable to use silica particles having silanol groups remaining on 90% or more of the particle surface.

[0027] [binder] The binder 11 can be appropriately selected depending on the abrasion resistance and environmental reliability of the hydrophilic coating and the adhesion to the silica particles 12, but it is preferable to use a silica binder that has high affinity with the silica particles 12 and improves the abrasion resistance of the porous layer. Among silica (SiO2) binders, it is more preferable to use a hydrolysis condensation product of silicate, and even more preferable to use a hydrolysis condensation product of tetrafunctional silicate.

[0028] The content of the binder 11 is preferably 3% by mass or more and 20% by mass or less, and more preferably 10% by mass or more and 20% by mass or less, relative to the total mass of the porous layer 14. If the content of the binder 11 relative to the total mass of the porous layer 14 is less than 3% by mass, the force fixing the silica particles 12 is weak, and the silica particles 12 may peel off. If the content of the binder 11 relative to the porous layer 14 exceeds 20% by mass, the spaces between the silica particles 12 are filled with the binder, reducing the porosity of the porous layer 14 and tending to increase the internal stress of the hydrophilic coating.

[0029] <Mixed layer> The mixed layer 15 is a layer in which the resin substrate 16 penetrates into the voids of the network structure formed by bonding silica particles together with a binder, and is provided on the side of the resin substrate 16 where the porous layer 14 is provided. The range from the top of the resin substrate 16 that penetrates into the voids of the network structure formed by the binder and silica particles to the bottom of the network structure is the mixed layer 15. When installed in an outdoor environment, the resin substrate 16 may be oxidized and deteriorated by sunlight and oxygen. However, the mixed layer can reduce the surface area of ​​the resin substrate 16 that comes into contact with oxygen, so that the oxidized deterioration of the resin substrate 16 can be suppressed. Furthermore, the mixed layer 15 and the porous layer 14 have a continuous network structure, which relieves stress associated with oxidative deterioration of the resin substrate 16 and suppresses the occurrence of cracks.

[0030] The thickness of the mixed layer 15 is preferably 20 nm or more and 160 nm or less. When the thickness of the mixed layer 15 is smaller than 20 nm, the resin substrate 16 does not sufficiently penetrate into the network structure, and the stress associated with the oxidative deterioration of the resin substrate 16 cannot be relieved, and the occurrence of cracks in the resin substrate 16 cannot be suppressed. When the thickness of the mixed layer 15 is larger than 160 nm, scattering occurs due to the resin substrate 16 and the silica particles 12, and the haze increases, which is not preferable. In addition, the thickness of the mixed layer is preferably larger than the average particle diameter of the silica particles. By making the thickness of the mixed layer larger than the average particle diameter of the silica particles, the strength of the network structure of the mixed layer 15 can be strengthened, and the occurrence of cracks can be more reliably suppressed. In addition, when chain-like silica particles are used, the thickness of the mixed layer is preferably larger than the average particle diameter of the individual particles connected to each other.

[0031] The volume ratio of the network structure in the mixed layer 15 is preferably 20% or more and 80% or less, and more preferably 30% or more and 70% or less. When the volume ratio of the network structure in the mixed layer 15 is 20% or more, oxidation deterioration of the resin substrate 16 during outdoor exposure can be sufficiently suppressed, and the occurrence of cracks can be suppressed. When the volume ratio of the network structure in the mixed layer 15 is 80% or less, stress during outdoor exposure can be alleviated, and the occurrence of cracks can be suppressed.

[0032] The mixed layer 15 also relieves stress caused by the expansion and contraction of the resin substrate 16 due to water absorption from rain or temperature changes due to sunlight. The film thickness of the mixed layer 15 has a film thickness variation of 15% or less in any 1 μm length range along the surface of the resin substrate 16 in the cross section in the thickness direction. If the film thickness variation of the mixed layer in the film surface is greater than 15%, stress caused by the expansion and contraction of the resin substrate is concentrated in the part where the mixed layer is thinner than the surrounding area, causing cracks in the resin substrate 16 and the hydrophilic coating. As a result, it is not possible to suppress an increase in haze and maintain hydrophilicity.

[0033] The film thickness variation is the ratio of the height of the unevenness occurring at the interface between the resin substrate 16 and the mixed layer 15 to the average film thickness of the mixed layer 15. The transparent member of the present invention is sliced ​​and the cross section is observed with a scanning transmission electron microscope or the like to determine the average film thickness of the mixed layer 15 and the height of the unevenness occurring at the interface between the resin substrate 16 and the mixed layer 15. Here, the height of the unevenness occurring at the interface between the resin substrate 16 and the mixed layer 15 is the absolute value of the difference in height in the thickness direction between the part consisting of only the resin substrate 16 present at the interface closest to the mixed layer and the part of the mixed layer 15 present closest to the resin substrate 16. When calculating the film thickness variation, it is preferable to binarize the obtained image with image processing software, since this makes it easier to distinguish between the substrate and the mixed layer (silica particles or binder). As shown in FIG. 4, when an arbitrary 1 μm length along the surface of the resin substrate 16 in a cross section in the thickness direction is represented by the range of the solid line in the figure, the height of the unevenness (film thickness variation) occurring at the interface between the resin substrate 16 and the mixed layer 15 corresponds to the ratio of the height of the unevenness to the average film thickness of the distance between the two white dashed lines (the distance indicated by the white arrows).

[0034] <Resin substrate 16> The material of the resin substrate 16 may be a transparent resin such as acrylic resin, polycarbonate, or polyester. The shape of the resin substrate 16 is not limited, and may be a plate or a film, or may be a flat plate or a shape having a curved, concave, or convex surface, such as a hemispherical dome shape. The transmittance of the resin substrate to visible light is preferably 50% or more.

[0035] <Manufacturing method> Next, an example of a method for producing a transparent member according to the present invention will be described. The method for producing a transparent member according to the present invention includes a step of forming a porous layer 14 and a mixed layer 15 on a resin substrate 16 .

[0036] The process of forming the porous layer 14 and the mixed layer 15 can be carried out by applying and drying a dispersion of silica particles 12 and a binder solution in this order onto the resin substrate 16, or by applying and drying a dispersion containing both the silica particles 12 and a component that will become the binder 11 onto the resin substrate 16. The method of applying a dispersion containing both the silica particles 12 and a component that will become the binder 11 is more preferable in that the composition inside the porous layer 14 becomes uniform.

[0037] The dispersion of the silica particles 12 is a liquid in which the silica particles 12 are dispersed in a solvent, and the content of the silica particles 12 is preferably 2% by mass or more and 10% by mass or less. A silane coupling agent or a surfactant may be added to the dispersion of the silica particles 12 in order to increase the dispersibility of the silica particles 12. However, if these compounds react with many of the silanol groups on the surface of the silica particles 12, the bond between the silica particles 12 and the binder 11 is weakened, and the abrasion resistance of the porous layer 14 is reduced, or the hydrophilicity of the porous layer 14 is reduced. Therefore, the content of the additives such as the silane coupling agent or the surfactant in the dispersion is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the silica particles 12.

[0038] The binder solution is preferably a solution of a silica binder that has a strong bond with the silica particles 12. The silica binder solution is preferably a solution mainly composed of a silicate hydrolysis condensate, which is produced by adding water, an acid, or a base to a silicate ester such as methyl silicate or ethyl silicate in a solvent and subjecting the mixture to hydrolysis and condensation.

[0039] The type of acid or base to be used may be appropriately selected in consideration of the solubility in the solvent and the reactivity with the silicate ester. The acid used in the hydrolysis reaction is preferably hydrochloric acid or nitric acid, and the base is preferably ammonia or various amines. The silicate hydrolysis condensate can be prepared not only by the silicate ester but also by neutralizing and condensing a silicate such as sodium silicate in water. The acid that can be used in the neutralization reaction is hydrochloric acid, nitric acid, etc. When preparing the silica binder solution, heating may be performed at a temperature of 80°C or less.

[0040] When a silica binder is used for the binder 11, trifunctional silane alkoxides substituted with organic groups, such as methyltriethoxysilane and ethyltriethoxysilane, can be added to the silica binder solution in order to improve solubility and application properties. The amount of trifunctional silane alkoxide added is preferably 10 mol % or less of the total silane alkoxides contained in the silica binder solution. If the amount added exceeds 10 mol %, the organic groups inhibit hydrogen bonding between silanol groups inside the binder, thereby reducing wear resistance.

[0041] When using a dispersion liquid containing both silica particles 12 and a component that will become the binder 11, the above-mentioned dispersion liquid of silica particles 12 and the binder solution may be prepared in advance and then mixed. Alternatively, the dispersion liquid may be prepared by adding the component that will become the binder 11 to the dispersion liquid of silica particles 12 and reacting them. When using the latter method to obtain a dispersion liquid containing silica particles 12 and a silica binder as a component that will become the binder 11, it is possible to prepare the dispersion liquid by adding a silicic acid ester, water, and an acid catalyst to the dispersion liquid of silica particles 12 and reacting them. A method of preparing a binder solution in advance and then mixing them is preferable in that the reaction of the component that will become the binder 11 can be controlled and the reaction state can be checked while preparing the dispersion liquid.

[0042] The amount of the component that becomes binder 11 in a dispersion liquid containing both silica particles 12 and a component that becomes binder 11 is preferably 3 parts by mass or more and 20 parts by mass or less, and more preferably 10 parts by mass or more and 20 parts by mass or less, per 100 parts by mass of the total of the silica particles and the component that becomes binder.

[0043] The solvent that can be used for the dispersion of the silica particles 12 and the silica binder solution must be capable of dissolving or dispersing them uniformly and forming a film with a uniform thickness of the mixed layer 15. Therefore, it is desirable to combine a solvent with a relatively high solubility for the resin substrate 16 and a solvent with a relatively low solubility. It is also desirable that the boiling point of the solvent with a relatively high solubility for the resin substrate 16 is higher than the boiling point of the solvent with a relatively low solubility for the resin substrate 16. By selecting the solvent in this way, the silica particles are uniformly aligned in the early stage of the film formation process, and a porous network structure with a high uniform alignment is formed. In the later stage of the film formation process, the proportion of the solvent with a high boiling point and a relatively high solubility increases, and the resin substrate 16 is rapidly dissolved, so that the porous network structure formed in the early stage of the film formation process penetrates into the resin substrate 16, and a uniform mixed layer 15 is formed.

[0044] Examples of solvents that have a relatively high solubility for the resin substrate 16 include ethers such as dimethoxyethane, diglyme, dioxane, diisopropyl ether, dibutyl ether, and cyclopentyl methyl ether; esters such as ethyl acetate, n-butyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, and propylene glycol monomethyl ether acetate; and various aliphatic or alicyclic solvents such as n-hexane, n-octane, cyclohexane, cyclopentane, and cyclooctane. Examples of the solvent include aromatic hydrocarbons, various aromatic hydrocarbons such as toluene, xylene, and ethylbenzene, various ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, 2-heptanone, and cyclohexanone, various chlorinated hydrocarbons such as chloroform, methylene chloride, carbon tetrachloride, and tetrachloroethane, and aprotic polar solvents such as N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and ethylene carbonate, and the like. In other words, it is preferable that the first solvent is at least one selected from the above solvents. As solvents having a relatively high solubility for the resin substrate 16, diglyme, dibutyl ether, propylene glycol monomethyl ether acetate, and 2-heptanone are preferably used.

[0045] Examples of solvents in which the resin substrate 16 has a relatively low solubility include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methylpropanol, 1-pentanol, 2-pentanol, cyclopentanol, 2-methylbutanol, 3-methylbutanol, 1-hexanol, 2-hexanol, 3-hexanol, 4-methyl-2-pentanol, 2-methyl-1-pentanol, 2-ethylbutanol, 2,4-dimethyl-3-pentanol, 3-ethylbutanol, 1-heptanol, 2-ethylbut ... Examples of the second solvent include monohydric alcohols such as ethanol, 2-heptanol, 1-octanol, and 2-octanol; dihydric or higher alcohols such as ethylene glycol and triethylene glycol; and ether alcohols such as methoxyethanol, ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and 1-propoxy-2-propanol, i.e., it is preferable that the second solvent is at least one selected from the above solvents. As a solvent having a relatively low solubility for the resin substrate 16, 2-propanol is preferably used.

[0046] In order to obtain the transparent member according to the present invention, it is sufficient to select and use from these exemplified solvents etc. such that there is a difference in boiling point between a solvent having a relatively high solubility for the resin substrate 16 and a solvent having a relatively low solubility for the resin substrate 16. In addition, in consideration of the boiling point of the solvent, it is also possible to mix and use two or more solvents from among those having a relatively high solubility and those having a relatively low solubility.

[0047] When a solvent having a relatively high solubility and a solvent having a relatively low solubility are mixed and used, the ratio of the solvent having a relatively high solubility is preferably 2% by mass or more and 30% by mass or less, and more preferably 10% by mass or more and 20% by mass or less. When the ratio is 2% by mass or more, a sufficient mixed layer can be formed, and when the ratio is 30% by mass or less, the mixed layer does not become too thick and the haze can be maintained in a good state.

[0048] Methods for applying the dispersion of silica particles 12 and the binder solution, or a mixture of these, include spin coating, blade coating, roll coating, slit coating, printing, dip coating, etc. When manufacturing a transparent member having a three-dimensional complex shape such as a concave surface, the spin coating is preferred from the viewpoint of uniformity of film thickness.

[0049] After applying the dispersion of silica particles 12 and the binder solution, or a dispersion of a mixture of them, the amount of solvent remaining in the porous layer and the mixed layer can be suppressed to improve the abrasion resistance. Therefore, it is preferable to provide a drying step and a curing step to form the porous layer and the mixed layer. The drying step and the curing step are steps for removing the solvent, promoting the reaction of the components that will become the binder 11, or promoting the reaction of the components that will become the binder 11 with the silica particles 12. The temperature of the drying step and the curing step is preferably 20°C or higher and 200°C or lower, more preferably 60°C or higher and 150°C or lower. If the temperature of the drying step and the curing step is lower than 20°C, the solvent remains and the abrasion resistance decreases. Also, if the temperature of the drying step and the curing step exceeds 200°C, the binder 11 hardens too much, and as a result, the porous layer 14 is more likely to crack. The solvent remaining in the porous layer 14 is 3.0 mg / cm 3 It is preferable that:

[0050] When the dispersion liquid of the silica particles 12 and the binder solution are applied in this order, the dispersion liquid of the silica particles 12 can be applied and subjected to a baking process once, and then the binder solution can be applied and subjected to a drying process and a hardening process to form a porous layer and a mixed layer.

[0051] In order to obtain the porous layer 14 with a desired thickness, the above-mentioned coating step, drying step and curing step may be alternately repeated several times.

[0052] <Imaging device> FIG. 2 is a schematic diagram showing an embodiment of the imaging device of the present invention, in which FIG. 2(a) is a fixed-point observation type surveillance camera, and FIG. 2(b) is a swivel type surveillance camera capable of pan-tilt-zoom driving. The imaging devices shown in FIGS. 2(a) and (b) have a transparent member (protective cover) 3 according to the present invention that functions as a protective cover on device bodies 1 and 2, and device bodies 1 and 2 are equipped with an optical system for acquiring video data. The transparent member 3 covers at least the optical system of device bodies 1 and 2, and protects them from dust and impact from the outside. The protective cover 3 in FIG. 2(a) is a flat box type, and the protective cover 3 in FIG. 2(b) is a hemispherical dome type, but the shape of the protective cover 3 is not limited to these.

[0053] An example of the configuration of an imaging device according to the present invention is shown in Fig. 3. The imaging device 30 has a space surrounded by a transparent member 10 including a porous layer 14, a mixed layer 15, and a resin base material 16, and a housing 36, and includes an optical system 31, an image sensor 32, an image engine 33, a compression output circuit 34, and an output unit 35 in the space.

[0054] The image captured through the transparent member 10 is guided to the image sensor 32 by the optical system (lens) 31, and is converted by the image sensor 32 into an analog video signal (electrical signal) and output. The analog video signal output from the image sensor 32 is converted into a digital video signal by the video engine 33, and the digital video signal output from the video engine 33 is compressed into a digital file by the compression output circuit 34. In the process of converting the analog video signal into a digital video signal, the video engine 33 may perform processing to adjust image quality such as brightness, contrast, color correction, and noise removal. The signal output from the compression output circuit 34 is output from the output unit 35 to an external device via wiring.

[0055] The transparent member 10 is installed so that the surface on which the porous layer 14 is provided faces the outside. This configuration provides protection from external dust and impacts, and also turns water droplets that adhere to the surface of the transparent member 10 due to changes in the external environment into a liquid film, thereby suppressing distortion of the image captured by the image sensor 32.

[0056] Furthermore, the imaging device 30 can form an imaging system together with a pan-tilt for adjusting the angle of view, a controller for controlling imaging conditions, a storage device for saving the acquired video data, and a transfer means for transferring data output from the output unit 35 to the outside. EXAMPLES

[0057] A specific method for producing the transparent member according to the present invention will now be described. (Preparation of Coating Fluid) First, the coating liquid used in the production of the transparent member according to the present invention will be described.

[0058] (1) Preparation of silica binder solution 13.82 g of ethanol and an aqueous nitric acid solution (concentration: 3%) were added to 12.48 g of ethyl silicate, and the mixture was stirred at room temperature for 10 hours to prepare a silica binder solution (solid concentration: 12.0% by mass).

[0059] (2-1) Preparation of silica particle coating solution A 20.00 g of a dispersion of chain-like silica particles in 2-propanol (IPA) (trade name: IPA-ST-UP, manufactured by Nissan Chemical Industries, Ltd., solid content concentration 15.5% by mass) was diluted with 85.00 g of IPA (boiling point: 82.5 ° C.) and 15.00 g of diglyme (boiling point: 162.0 ° C.) as a solvent, and then 2.60 g of the silica binder solution prepared in (1) was added and stirred at room temperature for 10 minutes. After that, the mixture was stirred at 50 ° C. for 1 hour to prepare silica particle coating liquid A. It was confirmed by particle size distribution measurement by dynamic light scattering method (trade name: Zetasizer Nano ZS, manufactured by Malvern Instruments) that chain-like silica particles in which silica particles with an average particle size of 15 nm are connected to an average of 95 nm in circle equivalent diameter were dispersed in the silica particle coating liquid A.

[0060] (2-2) Preparation of silica particle coating solution B Silica particle coating solution B was prepared in the same manner as silica particle coating solution A, except that 85.00 g of IPA and 15.00 g of dibutyl ether (boiling point: 140.8° C.) were used as the solvent.

[0061] (2-3) Preparation of silica particle coating solution C Silica particle coating solution C was prepared in the same manner as for silica particle coating solution A, except that 85.00 g of IPA and 15.00 g of propylene glycol monomethyl ether acetate (boiling point: 140.0° C.) were used as the solvent.

[0062] (2-4) Preparation of silica particle coating solution D Silica particle coating solution D was prepared in the same manner as for silica particle coating solution A, except that 70.00 g of IPA and 30.00 g of 2-heptanone (boiling point: 151.0° C.) were used as the solvent.

[0063] (2-5) Preparation of silica particle coating solution E Silica particle coating solution E was prepared in the same manner as silica particle coating solution A, except that 70.00 g of IPA and 30.00 g of diglyme were used as the solvent.

[0064] (2-6) Preparation of silica particle coating solution F Silica particle coating solution F was prepared in the same manner as for silica particle coating solution A, except that 100.00 g of IPA was used as the solvent.

[0065] (2-7) Preparation of silica particle coating solution G Silica particle coating solution G was prepared in the same manner as for silica particle coating solution A, except that 70.00 g of IPA and 30.00 g of tetrahydrofuran (boiling point: 66.0° C.) were used as the solvent.

[0066] (2-8) Preparation of silica particle coating solution H Silica particle coating solution H was prepared in the same manner as silica particle coating solution A, except that 105.00 g of IPA and 30.00 g of diglyme were used as the solvent.

[0067] Example 1 An appropriate amount of silica particle coating solution A was dropped onto a polycarbonate substrate (nd=1.58, νd=30.2) with a diameter (φ) of 50 mm and a thickness of 4 mm and a light transmittance of approximately 80%, and spin-coated at 2000 rpm for 20 seconds. It was then heated in a hot air circulating oven at 90°C for 15 minutes to create a transparent component with a porous layer and a mixed layer. The average Feret diameter of the silica particles was 15 nm.

[0068] 4 is a cross-sectional observation image of the transparent member produced in Example 1. From the bottom of the observation image, it can be seen that three layers are formed: a resin substrate 16, a mixed layer 15 of a resin substrate and silica particles, and a porous layer 14. The film thickness variation of the mixed layer 15, which will be described later, was calculated using this cross-sectional observation image, and the film thickness variation was 8%.

[0069] Example 2 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid B was used instead of the silica particle coating liquid A.

[0070] Example 3 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid C was used instead of the silica particle coating liquid A.

[0071] Example 4 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid D was used instead of the silica particle coating liquid A.

[0072] Example 5 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid E was used instead of the silica particle coating liquid A.

[0073] Example 6 The transparent member prepared in the same manner as in Example 1 was further coated with silica particle coating liquid F. The coating was performed by dropping an appropriate amount of silica particle coating liquid F, spin coating at 2000 rpm for 20 seconds, and heating in a hot air circulating oven at 90°C for 15 minutes. This series of steps was repeated twice to prepare a transparent member.

[0074] Comparative Example 1 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid F was used instead of the silica particle coating liquid A.

[0075] Comparative Example 2 The hydrophilic coated transparent member prepared in the same manner as in Example 1 was further coated with silica particle coating liquid F. The coating was performed by dropping an appropriate amount of silica particle coating liquid F, spin coating at 2000 rpm for 20 seconds, and heating in a hot air circulating oven at 90°C for 15 minutes. This series of steps was repeated three times to prepare a hydrophilic coated transparent member.

[0076] Comparative Example 3 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating solution G was used instead of the silica particle coating solution A.

[0077] Comparative Example 4 A transparent member was produced in the same manner as in Example 1, except that the silica particle coating liquid H was used instead of the silica particle coating liquid A.

[0078] (Evaluation method for transparent components) Next, a method for evaluating the transparent members produced in the examples and comparative examples will be described. (1) Measurement of the thickness of the porous layer and the mixed layer The thicknesses of the porous layer and the mixed layer were determined by measuring with a spectroscopic ellipsometer (product name: VASE, manufactured by J.A. Woollam Japan) in the wavelength range of 380 nm to 800 nm.

[0079] (2) Measurement of the porosity of the porous layer A spectroscopic ellipsometer (product name: VASE, manufactured by J.A. Woollam Japan) was used to measure from wavelengths of 380 nm to 800 nm, and the refractive index of the porous layer was determined from analysis. The porosity of the porous layer was then calculated using Equation 1.

[0080] (3) Measurement of the thickness variation of the mixed layer The membrane was cut out using a focused ion beam device (product name: SMI3050, manufactured by SII NanoTechnology) and sliced ​​so that the cross section of the mixed layer in the thickness direction could be observed. The cross section of the mixed layer in the thickness direction was observed in bright field at a magnification of 100,000 times using a scanning transmission electron microscope (product name: S-5500, manufactured by Hitachi High-Technologies). The observed images were then processed. Commercially available image processing software such as Image Pro PLUS (manufactured by Media Cybernetics) was used for image processing. In a given image area, the contrast was adjusted appropriately if necessary to calculate the thickness of the mixed layer, and the thickness variation within a length range of 1 μm was calculated.

[0081] (4) Contact angle measurement Using a fully automatic contact angle meter (product name: DM-701, manufactured by Kyowa Interface Science Co., Ltd.), the contact angle was measured when a 2 μl droplet of pure water was brought into contact at 23° C. and 50% RH.

[0082] (5) Haze measurement The haze was measured using a haze meter (product name: NDH2000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0083] (6) Outdoor exposure test The transparent member was placed in a xenon weather meter (product name: Super Xenon Weather Meter SX75, manufactured by Suga Test Instruments Co., Ltd.). The light irradiation intensity was 180 W / m 2 The test was performed for a total of 600 hours, with 300 cycles consisting of 18 minutes of light irradiation and water spray, and 1 hour and 42 minutes of light irradiation as one cycle. The contact angle of the transparent member after the test was measured in the same manner as in (4) Contact angle measurement. 100 hours of this outdoor exposure test corresponds to one year of actual outdoor exposure.

[0084] (7) Evaluation If the contact angle is 30° or less, the formation of water droplets on the surface of the transparent material can be sufficiently suppressed. Also, if the haze is 1 or less, a clear image can be obtained when photographing. Therefore, if the contact angle was 30° or less and the haze was 1 or less in both the initial value and the value after the outdoor exposure test, it was evaluated as good, and if either the contact angle was more than 30° or the haze was more than 1, it was evaluated as poor.

[0085] (8) Surface roughness measurement The surface shape in an area of ​​2 μm×2 μm was measured using an SPM (product name: L-trace&NanoNaviII, manufactured by SII Nano Technology Co., Ltd.), and Ra was calculated therefrom. The measurement results and evaluation results for Examples 1 to 6 and Comparative Examples 1 to 4 are shown in Table 1.

[0086] [Table 1]

[0087] As shown in Table 1, it was confirmed that the contact angle was 30° or less and the haze was 1 or less both at the initial value and after outdoor exposure, and that the configuration of this example could maintain hydrophilicity and haze. On the other hand, Comparative Example 1, which is outside the scope of the present invention because a mixed layer is not provided, Comparative Example 2, in which the thickness of the porous layer is thicker than the range specified in the present invention, Comparative Example 4, in which the thickness of the porous layer is thinner than the range specified in the present invention, and Comparative Example 3, in which the thickness variation of the mixed layer is larger than the range specified in the present invention, were unable to maintain hydrophilicity after outdoor exposure and suppress an increase in haze. [Industrial Applicability]

[0088] The transparent member of the present invention is not limited to applications in imaging devices, such as flat covers and dome covers for outdoor cameras and surveillance cameras, but can also be used for general applications such as window glass, mirrors, lenses, and transparent films, as well as optical lenses, optical mirrors, optical filters, eyepieces, and optical components in imaging systems and projection systems. [Explanation of symbols]

[0089] 10 Transparent materials 11. Binder 12 Silica particles 13 void 14 Porous layer 15 Mixed layer 16 Resin substrate 1. Device body 2. Device body 3 Transparent parts (protective covers) 30 Imaging device 31 Optical system (lens) 32 Image Sensor 33 Video Engine 34 Compression output circuit 35 Output section 36 Case

Claims

1. A coating liquid comprising chain silica particles, a silicate hydrolysis condensate, and a solvent, The solvent is at least one first solvent selected from the group consisting of ethers, esters, aliphatic or alicyclic hydrocarbons, aromatic hydrocarbons, ketones, chlorinated hydrocarbons, and aprotic polar solvents; a second solvent which is at least one selected from the group consisting of monohydric alcohols, dihydric or higher alcohols, and ether alcohols, and has a boiling point lower than that of the first solvent; Including, A coating liquid having a content of the silicate hydrolysis condensate of 3 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the total of the chain silica particles and the silicate hydrolysis condensate.

2. 2. The coating fluid according to claim 1, wherein the content of the chain silica particles is from 2% by mass to 10% by mass.

3. A coating liquid comprising chain silica particles, a silicate hydrolysis condensate, and a solvent, The solvent is at least one first solvent selected from the group consisting of ethers, esters, aliphatic or alicyclic hydrocarbons, aromatic hydrocarbons, ketones, chlorinated hydrocarbons, and aprotic polar solvents; a second solvent which is at least one selected from the group consisting of monohydric alcohols, dihydric or higher alcohols, and ether alcohols, and has a boiling point lower than that of the first solvent; Including, A coating liquid having a content of the chain silica particles of 2% by mass or more and 10% by mass or less.

4. The coating fluid according to any one of claims 1 to 3, characterized in that the first solvent contains at least one selected from the group consisting of dimethoxyethane, diglyme, dioxane, diisopropyl ether, dibutyl ether, cyclopentyl methyl ether, ethyl acetate, n-butyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, 2-heptanone, and cyclohexanone.

5. The coating liquid according to any one of claims 1 to 4, characterized in that the second solvent contains at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methylpropanol, 1-pentanol, 2-pentanol, cyclopentanol, 2-methylbutanol, 3-methylbutanol, 1-hexanol, 2-hexanol, 3-hexanol, 4-methyl-2-pentanol, 2-methyl-1-pentanol, 2-ethylbutanol, 2,4-dimethyl-3-pentanol, 3-ethylbutanol, 1-heptanol, 2-heptanol, 1-octanol, 2-octanol, ethylene glycol, triethylene glycol, methoxyethanol, ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and 1-propoxy-2-propanol.

6. The coating fluid according to claim 1 , wherein a ratio of the first solvent to the solvent is from 2% by mass to 30% by mass.

7. 7. The coating fluid according to claim 1, wherein the chain silica particles have an average Feret's diameter of 10 nm or more and 60 nm or less.

8. A step of providing the coating liquid according to any one of claims 1 to 7 on a resin substrate; and curing the coating liquid to form a mixed layer on the resin substrate. The thickness of the mixed layer is 20 nm or more and 160 nm or less, A method for producing a member, wherein the mixed layer has a thickness variation of 15% or less within a 1 μm length range along the surface of the resin substrate in a cross section in the thickness direction.

9. In the forming step, a porous layer is formed on the mixed layer, 9. The method for manufacturing a member according to claim 8, wherein the porous layer has a thickness of 100 nm or more and 800 nm or less.

10. 10. The method for manufacturing a member according to claim 8, wherein the resin substrate is made of one or more materials selected from the group consisting of acrylic resin, polycarbonate, and polyester.

Citation Information

Patent Citations

  • Antifog and antifouling agent for organic substrate, and method for coating organic substrate with the antifog and antifouling agent

    JP2013203774A

  • Coating liquid, method for producing coating liquid, method for producing laminated film and method for producing image display device

    JP2017066209A

  • Optical member and imaging apparatus

    JP2018116177A